Exploring the Dimensions and Determinants of Islamic Ethical Marketing in SMEs in Promoting Sustainable Entrepreneurship: A Systematic Literature Review - Zulkhulafair Muchtar; Fitriany; Didiek Handayani Gusti (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This study aims to explore the conceptual development and dimensions of Islamic value-based ethical marketing within small and medium-sized enterprises (SMEs), to identify the principal determinant factors, and to analyze its relationship with business performance and sustainability (sustainable entrepreneurship). The method employed is a non-systematic literature review of 38 journal articles indexed in Scopus, relevant to the topics of Islamic business ethics, SMEs, financial literacy, innovation, ethical leadership, and digitalization. The analytical process was conducted through thematic analysis techniques to categorize findings into conceptual dimensions, determinant factors, and their relationships with business performance and sustainability. The findings indicate that Islamic value-based ethical marketing has evolved from a normative approach into an integrative one, encompassing spiritual values, regulatory frameworks, and technology. Furthermore, financial literacy, innovation, ethical leadership, and digital transformation were identified as the primary factors influencing the implementation of ethical marketing. The findings also demonstrate that ethical marketing is associated with business performance and sustainability through various mechanisms, including social responsibility, financial behavior, and technological adaptation. The conclusions of this study affirm that Islamic value-based ethical marketing constitutes a strategic approach that supports the sustainability of SMEs, and requires a multidimensional integration of values, internal capacity, and technology in its implementation.